Evaluation of Soft Contact Lens Performance Using the Contrast Sensitivity Function - Timpano, V (Canadian Journal of Optometry, 2021)
The contrast sensitivity function (CSF) has been widely accepted as a measure of visual performance. Its use as a diagnostic tool in contact lens work has been documented. Typically, the CSF has been used for the patient who presented with a complaint of blurred vision while wearing hydrogel contact lenses. Snellen visual acuity testing indicated little, or no decrease in vision. The contrast sensitivity test on the other hand, indicates a reduction in visual performance. Studies have shown that this reduction is usually due to a small residual refractive error, or to deposits on the lens. It sometimes happens that patients who have been wearing soft contact lenses successfully for some years require a new lens. Upon delivery of the new lens the patient does not achieve the expected performance.